Pengembangan Media Monopoli Edukatif di Kelas IV Sekolah Dasar - Yunita Wildaniati (Faculty of Education Universitas Negeri Malang, 2017)
Abstract: This study aims to produce an educative monopoly media product that is valid according to the expert and effective according to the user. In addition, it is expected to improve student learning outcomes. Research methods used by researchers in research and development. This educative monopoly media is a modified research and development model by the researcher himself. The steps of research and development model are: (1) identification of needs; (2) product design; (3) production; (4) product validation; (5) product revisions; (6) trial usage; and (7) revision of the final product. After going through the steps of research and development, the researchers conducted an analysis of the data obtained. The results of the researcher’s analysis show that this educative monopoly media is very effective in attracting students’ attention to learn and very effective in improving the result of fourth grade student of Public Elementary School 4 Malang (SDN Pandanwangi 4 Malang). Based on the results of research and development of this educative monopoly media, it is expected that fourth grade teachers to use this educative monopoly media in learning, as well as maintaining and storing the media of educative monopoly well after using it. In addition, other researchers are also expected to test this educative monopoly media in other schools to see its effectiveness. Abstrak: Penelitian ini bertujuan untuk menghasilkan sebuah produk media monopoli edukatif yang valid menurut ahli dan efektif menurut pengguna. Selain itu, diharapkan dapat meningkatkan hasil belajar siswa. Metode penelitian yang digunakan peneliti dalam penelitian dan pengembangan. Media monopoli edukatif ini yaitu model penelitian dan pengembangan hasil modifikasi oleh peneliti sendiri. Langkah-langkah model penelitian dan pengembangannya yaitu: (1) identifikasi kebutuhan; (2) desain produk; (3) produksi; (4) validasi produk; (5) revisi produk; (6) uji coba pemakaian; dan (7) revisi produk akhir. Setelah melalui langkah-langkah penelitian dan pengembangan, peneliti melakukan analisis terhadap data-data yang didapatkan. Hasil analisis peneliti menunjukkan bahwa media monopoli edukatif ini sangat efektif dalam menarik perhatian siswa untuk belajar serta sangat efektif dalam meningkatkan hasil belajar siswa kelas IV SDN Pandanwangi 4 Kota Malang. Berdasarkan hasil penelitian dan pengembangan media monopoli edukatif ini, diharapkan guru kelas IV untuk menggunakan media monopoli edukatif ini dalam pembelajaran, serta merawat dan menyimpan media monopoli edukatif dengan baik setelah menggunakannya. Selain itu, diharapkan juga peneliti lain mengujicobakan media monopoli edukatif ini di sekolah lain untuk melihat keefektifannya.